2021
DOI: 10.3389/fonc.2021.812207
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of AML Relapse After Allo-HCT

Abstract: With advances in allogeneic hematopoietic stem cell transplant (allo-HCT), disease relapse has replaced transplant-related mortality as the primary cause of treatment failure for patients with acute myeloid leukemia (AML). The efficacy of allo-HCT in AML is a consequence of a graft-versus-leukemia (GVL) effect that is mediated by T lymphocytes, and unique mechanisms of immune evasion underlying post-allo-HCT AML relapses have recently been characterized. Relapsed AML following allo-HCT presents a particularly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 111 publications
0
16
0
1
Order By: Relevance
“…Despite the expansion of targeted therapies for AML patients, as well as other approaches such as post-transplant maintenance therapy, relapse of AML remains the main cause of mortality in patients with this entity. The exceptionally poor prognosis in this patient group is aggravated further by the very limited availability of registered therapy options at this stage and the rapidly progressive nature of their disease 3 . Thus, improving the prognosis of patients at relapse of AML that have exhausted all registered therapy options remains a critical unsolved issue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the expansion of targeted therapies for AML patients, as well as other approaches such as post-transplant maintenance therapy, relapse of AML remains the main cause of mortality in patients with this entity. The exceptionally poor prognosis in this patient group is aggravated further by the very limited availability of registered therapy options at this stage and the rapidly progressive nature of their disease 3 . Thus, improving the prognosis of patients at relapse of AML that have exhausted all registered therapy options remains a critical unsolved issue.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the screening procedure is fast, taking a median of only 5 days to deliver the necessary results and new therapy protocols could be administered within a median of 11 days after receiving the pharmacoscopy results. Thus the procedure does not significantly slow down clinical decision-making, which is a key concern in a rapidly progressing disease such as AML at relapse 1,3 .…”
Section: Discussionmentioning
confidence: 99%
“…Currently available treatments, including intensive chemotherapy, DLI, etc., were partially hindered by poor efficacy and toxicity ( 2 , 4 , 19 ). Previous researches on IC treatment for post-transplantation AML relapse have demonstrated CR rates from 13% to 71% and 1-year OS from 25% to 34.4% ( 20 ). A recent study including 175 patients showed a remission rate of 36% and median OS of 188 days, while early mortality within 28 days occurred in 12% patients ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, they are still at risk for drug resistance and disease recurrence, thus resulting in shorter survival and poorer International Journal of General Medicine 2023:16 1491-1504 quality of life. 3 Studying the molecular mechanism of AML development takes on a great significance in finding novel therapeutic targets and facilitating AML prognosis.…”
Section: Introductionmentioning
confidence: 99%